On unsteady reacting flow in a channel with a cavity - Ivar Ø. Sand (Modeling, Identification and Control, 1991)
The problem investigated is the stability of a flame anchored by recirculation within a channel with a cavity, acting as a two-dimensional approximation to a gas turbine combustion chamber. This is related to experiments of Vaneveld, Hom and Oppenheim (1982). The hypothesis studied is that hydrodynamic oscillations within the cavity can lead to flashback.